Connectivity Between Pedestrian Ways and BRT Shelter in Banyumanik and Pedurungan, Semarang - Dewi, Diah Intan; Rakhmatulloh, Anita Ratnasari (Semarang State University, 2018)
The increasing number of human activities from sub urban areas causes high movements in urban areas. The high rate of human movement drives the need for human circulation pathways and adequate transportation systems. To solve this problem, the Semarang City government has actually built transportation facilities in the form of BRT (Bus Rapid Transit) along with pedestrian ways. However, in reality the pedestrian ways that acts as a link to the door to door service is not well connected so it is less secure and comfortable and unable to accommodate the needs of the urban community. The purpose of this study was to examine the connectivity between pedestrian networks and BRT shelter in Semarang. The method of analysis in this study used GIS applications to evaluate access pedestrian connectivity to BRT shelther in Banyumanik and Pedurungan, Semarang. The results of the study are the connectivity between pedestrian ways and BRT shelterÃ‚Â in Banyumanik is good on the other side the connectivity in Pedurungan is not good and optimally configured